Introduction to the Special Issue: Claiming Unity and Diversity in Qualitative Psychology. (February 2014) - Gemignani, Marco; Brinkmann, Svend; Benozzo, Angelo; Cisneros Puebla, César A.
In this article, we position the special issue and explore some of the common interests and voices that tend to be shared among the field of qualitative psychology and the authors and assays that appear in the following pages. In doing this, we draw the contours of qualitative psychology that, in our view, is characterized mainly by the appreciation of complexity of knowledge, by the strong belief in the relational and collaborative view of the process of creating knowledge and acting on it, and finally by the effort to promote social justice through the findings of the research.